1987
DOI: 10.1093/geronj/42.5.519
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks in Adult Life and a Preliminary Examination of the Convoy Model

Abstract: This paper examines the social support networks of older adults. Based upon the Kahn and Antonucci (1980) life course social support model, a national sample of adults aged 50 and older (N = 718) was interviewed, generating support networks consisting of an average of 8.9 members. The respondents were asked questions of the structural (e.g., age, sex, closeness, years known, proximity, and frequency of contact) and functional (number and type of supports provided and received) characteristics of their social n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
527
3
17

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 707 publications
(568 citation statements)
references
References 4 publications
21
527
3
17
Order By: Relevance
“…This is consistent with the literature that shows rather low levels of communication about chronic disease FHH among the public (Yoon et al 2004) and highlights our missed opportunities in chronic disease prevention especially among those at increased risk due to family history. The average size of the currently living network and levels of support exchange reported by the participants in this study were similar (Antonucci and Akiyama 1987) or slightly smaller than previously reported (Ashida and Heaney 2008) and is likely due to the current study's focus on the FHH communication network rather than an overall social support network. Disseminating FHH information to biological children is especially important because these adult children can later inform the younger family members when they reach an appropriate age.…”
Section: Discussionsupporting
confidence: 60%
“…This is consistent with the literature that shows rather low levels of communication about chronic disease FHH among the public (Yoon et al 2004) and highlights our missed opportunities in chronic disease prevention especially among those at increased risk due to family history. The average size of the currently living network and levels of support exchange reported by the participants in this study were similar (Antonucci and Akiyama 1987) or slightly smaller than previously reported (Ashida and Heaney 2008) and is likely due to the current study's focus on the FHH communication network rather than an overall social support network. Disseminating FHH information to biological children is especially important because these adult children can later inform the younger family members when they reach an appropriate age.…”
Section: Discussionsupporting
confidence: 60%
“…A robust body of literature indicates that parents provide considerable financial support (Schoeni and Ross 2005;Yelowitz 2007) and frequently listen to their children and give them advice, typically around a few times a month, during emerging and young adulthood (Fingerman et al 2016(Fingerman et al , 2009(Fingerman et al , 2010Pettit et al 2011). Theories of intergenerational support (Antonucci and Akiyama 1987;Becker 1981) identify four reasons for parents' continuance of support: (a) to help children in need (altruism), (b) to maximize reproductive success (evolution), (c) to derive support from children in older adulthood (exchange), and (d) to improve chances for success (investment). As such, Fingerman and colleagues (2009) found that parents provided more financial and practical support to youth in need (e.g., experienced financial or health problems, younger in age) and more listening and advice support to youth viewed as successful (e.g., educational or career achievement).…”
Section: Developmental Psychology Literature Characterizing Parental mentioning
confidence: 99%
“…Nesta pesquisa, os círculos concêntricos estão atrelados ao suporte que os profissionais da saúde disponibilizam às famílias do seu território de atuação. Assim, as características do círculo interno representam os profissionais tidos como de referência, os quais são procurados preferencialmente em detrimento dos que estão nos círculos intermediário e externo (4) . Logo, escolheu-se o círculo interno por entender que este melhor representa o suporte disponibilizado pelas relações que acontecem neste círculo.…”
Section: Discussionunclassified
“…Cada pessoa inserida nessa rede tem uma relação diferente com a pessoa investigada (4) . O comboio possui três círculos concên-tricos, os quais rodeiam o sujeito.…”
Section: Métodounclassified
See 1 more Smart Citation